Design of Reservation and Customer Management Information System at Polka Barbershop Using Laravel Framework - Muhammad Abrar Farid Almaarij; Umar Mansyuri; Rahadian Arief (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
The advancement of digital technology has driven service-based businesses, including barbershops, to implement information systems to enhance operational efficiency. Polka Barbershop, located in Serang City, still utilizes manual methods for managing reservations and customer data, leading to disorganized queues, limited access to digital transactions, and challenges in generating reports. This study aims to design a web-based reservation and customer management information system using the Laravel framework. The system was developed following the waterfall model, encompassing stages such as requirements analysis, system design with UML diagrams, implementation, and testing through Blackbox and User Acceptance Testing (UAT). Key features of the system include online booking, real-time queue management, Midtrans payment gateway integration, and automated report generation. Testing results indicate that the system meets user requirements, improves service speed, and enhances the accuracy of customer data. The findings suggest that implementing a web-based information system can substantially improve service quality and operational efficiency in barbershops, offering a scalable solution for similar businesses.